Fast talk Italian : guaranteed to get you talking - Iagnocco, Pietro; Coates, Karina; Walker, Susie; Cicioni, Mirna; Beltrami, Anna (Fast talk., 2023)
"Although you can get by in Italy without speaking the language, knowing just a few essential phrases can help you make friends, enjoy service with a smile, and discover richer, more rewarding travel experiences. Fast Talk Italian is the concise language guide that is guaranteed to get you talking with confidence. Experience a delicious meal at a no-menu trattoria, find a hidden art gallery off the tourist trail, or discover the best cappuccino in Rome. Essential phrases to meet all your travel needs. How to get local recommendations. Easy-to-use pronunciation guides. Expert tips to boost your confidence"--Publisher's description.